Extraction of biological apatite from cow bone at different calcination temperatures: a comparative study - Bano, Nazia; Sharifah Adzila, Syed Abu Bakar; Jikan, Suzi Salwah; Basri, Hatijah; Kanasan, Nanthini (Trans Tech Publications, 2019)
The purpose of this study is to extract natural hydroxyapatite (HAP) from cow bone. The hydrothermal method followed by calcination treatment at different temperatures is used in this current research. Cow bone has the potential for producing hydroxyapatite, a chief component present in bone and teeth of vertebrates. HAP is an excellent material used in bone restoration and tissue regeneration. Characterizations of the cow bone natural HAP powder were done by X-ray diffraction (XRD) and Thermogravimetric analysis (TGA). TGA data revealed that biological apatite is thermally stable at 1100ºC. XRD data showed that the extracted HAP is, highly crystalline and hexagonal crystal structure having a crystallite size in the range of 10-83 nm. The extracted HAP material is found to be thermally stable up to 1300ºC.